Effect of date powder and peach pomace powder on the microstructure and functional attributes of cookies - Shabnam, Shahida; Dar, Aamir Hussain; Aga, Mohsin Bashir; Khan , Shafat Ahmad (Journal of Postharvest Technology, 2020)
The effect of partial replacement of wheat flour with a 1:1 mixture of peach pomace powder and date palm fruit powder of cookies was  studied. Date powder and peach pomace powder were incorporated into wheat flour at different levels (2, 4, and 6%) and their effects  on the quality of cookies were investigated. The water absorption gradually increased by increasing the levels of peach and date  powder. Incorporation of date and peach powder mixture decreased the spread ratio and diameter of the cookies from 52.18 to 46.42  mm and 51.93 to 49.03 mm respectively, while the thickness increased from 9.86 to 10.56 mm. However, the hardness decreased  with an increase in the addition of the date and peach powder mixture concentration. Moisture, ash, crude fiber, protein, and fat  content were found higher in cookies prepared from the different percentage of date and peach powder mixture. Air spaces were  visualized in the case of the control sample and these spaces decreased with an increase in the concentration of date and peach  powder. Supplementation of date and peach powder of a 6 % level showed gelatinized starch granules trapped in the protein matrix.
Keywords: Cookies; peach powder,; date fruit; wheat flour; nutritional quality; color